An Analysis Of Slang Words On Comments Of Podcast On Youtube Channel”Curhat Bang Denny Sumargo” - Anita Sitanggang; Nikita Gabriella Sitanggang (Journal on Education, 2023)
The purpose of this research is to determine the types and meanings of slang words used by a podcast from YouTube channel “CURHAT BANG Denny Sumargo”. This research applies Mattiello's (2008) theory about various types of slang words. This research is descriptive qualitative research. The data were taken from captions of podcast that have been uploaded by YouTube channel “CURHAT BANG Denny Sumargo” in October 2022. This research finds that there are six types of slang by Mattiello used in podcast “Gagal bikin anak di Malaysia, air mata Lucinta Luna tumpah disini”, including acronym or initialism, clipping, compounding, reduplicative, variation, and word manufacture and fanciful formation. From six types of slang discovered, acronym is the most used slang on the podcast. On the other hand, the podcast used some clipping, reduplicative, and word manufacture. This research finds that more than 50% of Mattiello’s slang words used in the podcast.